MARKET DICIPLINE DAN REGULASI PENJAMINAN SIMPANAN BANK DI INDONESIA - Rahmat Setiawan; I Made Sudana (Jurnal Manajemen, 2016)
This research aims to find out the effect of fundamental factors bank as measured using the CAMEL ratio to changes the amount of deposits and interest rates. CAMEL ratios consists of capital as measured by capital adequacy ratio (CAR), asset quality as measured by non performing loan (NPL), management quality as measured by non-interest expenditures to total assets (NIETA), earnings as measured by return on assets (ROA), liquidity as measured by cash to assets (CTA). Research conducted in Indonesia is also used to find out if there are differences in the behavior of market discipline at the time of a full guarantee, Rp. 100 million guarantee, and Rp 2 billion guarantee. The results showed while guaranteeing full there was no fundamental factors influential to changes in bank deposits and interest rates, while the granting of Rp. 100 million CAR and CTA have significant positive effect to changes deposits and significant negatife to interest rates, and than NIETA has significant negative to changes deposits and significant positive to interest rates, Rp 2 billion guarantee CAR and ROA have positive effect to changes in deposits and significant negative to interest rates. Market discipline occurs at the time of the granting of Rp 2 billion and is increasing at the moment of granting decrase to Rp. 100 million, indicated by number of variables that has a significant effect to changes in deposit and interest rate. whereas when full guarantee market discipline does not occur.